Holographic Display System Based on Effective Area Expansion of SLM - Di Wang; Dan Xiao; Nan-Nan Li; Chao Liu; Qiong-Hua Wang (IEEE Photonics Journal, 2019)
In this paper, a holographic display system with wide viewing area is proposed based on the effective area expansion of the SLM. The effective area of the SLM is calculated based on the viewing area characteristics and expanded by using two SLMs. Different from the traditional holographic system based on the parallel-arranged SLMs or curved-arranged SLMs, we calculate the effective areas of the SLMs and the effective hologram of the system can be generated based on the effective-viewing-area (EVA) algorithm. The proposed system uses a 4K SLM by seamlessly stitching the effective areas of two 2K SLMs. After the EVA is calculated, the size of the effective hologram is inversely calculated according to the EVA. So, the effective area of the hologram is increased, and the calculation of the wasted information is greatly decreased. With the proposed system, the reconstructed object with large viewing area can be realized. Moreover, the calculation time for generating the hologram is reduced significantly. Experimental results verify the feasibility of the proposed system. In the proposed system, the 2K SLMs are used as examples for splicing, when more high-performance SLMs are used, the viewing area will be further expanded, and the advantage of the calculation speed will be more obvious than the traditional splicing method. The proposed system can provide new references to the holographic display system based on multiple SLMs stitching.